Carbon Nanomaterials as Adsorbents for Environmental and Biological Applications - Bergmann, Carlos P.; Machado, Fernando Machado; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book presents a summary of the current use of carbon nanomaterials for water treatment, drug delivery, systems and nanosensors. The first chapter elucidates the adsorption process phenomenon. Also, the properties of different carbon nanomaterials for adsorption applications are covered. The third chapter presents the kinetic and equilibrium models of adsorption, processing of experimental data and adsorption process peculiarities. Environmental and biological applications of carbon nanomaterials are listed in the last chapter. This book is written from an application-oriented perspective and is useful for all those interested in nanoadsorbents.
Preface -- Introduction -- Carbon Nanoadsorbents -- Kinetic and Equilibrium Models of Adsorption -- Experimental Adsorption -- Environmental Applications -- Molecules with Biological interest adsorbed on Carbon Nanostructures.
Keywords: Materials science; Nanochemistry; Nanotechnology; Environmental engineering; Biotechnology; Materials Science; Nanotechnology; Nanochemistry; Environmental Engineering/Biotechnology.; Nanotechnology and Microengineering; Electronic books